Integrated Multi-Trophic Aquaculture (IMTA) as a Solution for Shrimp Aquaculture Side Effects on Northern Coast of Java, Indonesia - Muhammad Rahmad Royan (Grouper: Fisheries Scientific Journal, 2020)
Along the northern coast of Java, Indonesia, shrimp aquaculture has been one of the main sources of income for coastal communities. Considering its benefits, not only does these aquaculture activity invite stakeholders to establish large-scale aquacultures, but it also triggers local people to set up family-scale aquaculture on their house yards. This practice, however, gradually aggravates the environmental and ecological aspects of the coast as there is no significant environmental impact assessment either by the players or by the municipality. Meanwhile, Integrated Multi-Trophic Aquaculture (IMTA) has been suggested to be able to overcome environmental and ecological side effects of aquaculture activities. In addition, IMTA can be beneficial for local people as the use of lower trophic organisms, such as mussels and seaweed in this method can be a source of livelihood. Pursuant to these facts, the implementation of IMTA is crucial for the environment, ecology and economic states of aquaculture in the northern coast of Java.